A new suppression strategy of pitching vibration based on the magnetic-electric-mechanical coupling dynamic model for superconducting EDS transport system. (1st April 2023) - Li, Hengda; Zhu, Hanlin; Huang, Huan; Li, Haitao; Deng, Zigang; Zheng, Jun
Highlights: A magnetic-electric-mechanical coupling dynamic model for EDS is established. The dynamic levitation force is verified by comparison with test results. The pitching vibration mechanism of the bogie is analyzed. A non-uniform exciting currents supply strategy is proposed and verified. Abstract: The superconducting electrodynamic suspension (EDS) train is suitable for high-speed maglev rail transit because of its low drag force, strong levitation force, large suspension gap, and so on. However, the electromagnetic forces of four pairs of superconducting coils on one bogie are dynamically unequal in practical operation. This causes the bogie to vibrate in the pitching axis, which affects the train system's safety, stability, and comfort. Therefore, proposing an appropriate strategy to suppress the bogie pitching vibration is significant. First, based on the dynamic circuit theory, energy method and rigid body dynamics, the magnetic-electric-mechanical coupling dynamic model of eight superconducting high-field coils in the bogie and ground null-flux coils was established to explore the characteristics of fluctuating and unequal electromagnetic forces. The synchronous current and motion responses were further calculated using the Runge-Kutta algorithm. Second, the bogie's vibration characteristics were analyzed and the reasons for the vertical and pitching vibration were discussed. And the accuracy of the model was verified by comparing the levitation force with the experiment data. Third, a non-uniform exciting currents supply strategy for the superconducting coils was proposed under the comprehensive evaluation of the suppressing effect on the pitching vibrations. Finally, several cases were given to prove the effectiveness of the strategy. The results show that the total electromotive force increased by 0.005% after adopting the proposed non-uniform exciting currents supply strategy. But the minimum and maximum amplitude of pitching vibration and the growth rate of pitching vibration decreased by 97.00%, 95.76%, and 81.45%, respectively. This new strategy can effectively suppress the pitching vibration of the bogie without changing the already-designed mechanical structure. This established magnetic-electric-mechanical coupling dynamic model and the suppression strategy provide reference and a new idea for the superconducting EDS system's safety, stability, and comfort.